Regional winners and losers in future UK energy system transitions. (November 2016) - Li, Francis G.N.; Pye, Steve; Strachan, Neil
Abstract: This paper demonstrates the integration of institutional perspectives on energy system transitions into formal energy economic modelling. The perspectives of key UK energy system stakeholders have been used to develop three socio-technical narratives of energy system change that are quantified in a 24-region techno-economic model of the country. Implementing these three narratives in the model environment allows their feasibility for meeting climate targets to be assessed as well as articulating their implied sub-national regional outlooks for technologies and investment. The latter elements are discussed in light of the regional socioeconomic and demographic landscape. The study highlights some of the regional political dimensions associated with future investment targeting in the UK energy system. In particular, energy policy decisions may create tensions between the four different UK government administrations as well as raising important questions about regional economic development and how an equitable energy transition can be achieved for all. Highlights: Prominent UK transition scenarios adapted into a whole energy system model. Integration process bridges between socio-technical theory and energy economic modelling. Model spatial detail used to relate geographical impacts to real-world regional actors. Tensions exposed between sub-regional optimality and national optimality. Discussion framed around the complex regional political geography of the UK.